2010
DOI: 10.1104/pp.110.157370
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Arabidopsis PAL Gene Family in Plant Growth, Development, and Response to Environmental Stress    

Abstract: Phenylalanine ammonia-lyase (PAL) catalyzes the first step of the phenylpropanoid pathway, which produces precursors to a variety of important secondary metabolites. Arabidopsis (Arabidopsis thaliana) contains four PAL genes (PAL1-PAL4), but there has been no genetic analysis to assess the biological functions of the entire gene family. Here, we report the generation and analysis of combined mutations for the four Arabidopsis PAL genes. Contrary to a previous report, we found that three independent pal1 pal2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
579
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 754 publications
(615 citation statements)
references
References 43 publications
30
579
0
6
Order By: Relevance
“…Unexpectedly, we found that the transcripts of ICS1 (Glyma01g25690) were repressed by 8-fold in GmMPK4-silenced plants. This suggests that the overaccumulation of SA in GmMPK4-silenced plants occurs in an ICS1-independent manner, possibly from precursors derived from the PAL pathway (Ribnicky et al, 1998;Huang et al, 2010), which would be consistent with the induction of genes encoding PALs. Alternatively, SA production is GmICS1 dependent, but GmICS1 expression is under negative feedback regulation by its own product, SA.…”
Section: Gmmpk4 Negatively Controls Sa and H 2 O 2 Levelsmentioning
confidence: 65%
“…Unexpectedly, we found that the transcripts of ICS1 (Glyma01g25690) were repressed by 8-fold in GmMPK4-silenced plants. This suggests that the overaccumulation of SA in GmMPK4-silenced plants occurs in an ICS1-independent manner, possibly from precursors derived from the PAL pathway (Ribnicky et al, 1998;Huang et al, 2010), which would be consistent with the induction of genes encoding PALs. Alternatively, SA production is GmICS1 dependent, but GmICS1 expression is under negative feedback regulation by its own product, SA.…”
Section: Gmmpk4 Negatively Controls Sa and H 2 O 2 Levelsmentioning
confidence: 65%
“…PAL is an indication of higher production of other secondary metabolites for resistance to pathogenesis and environmental stress (Huang et al 2010). It has been found that flavonoids and other phenolic compounds inhibit pathogens ranging from bacteria to fungi and insects (Hassan and Mathesius 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have recognized the contribution and control of PAL expression during the development of Arabidopsis, bamboo, olive, kenaf, and melon (Diallinas and Kanellis 1994;Ortega-García et al 2009;Huang et al 2010;Gao et al 2012;Jeong et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAL is a tetrameric enzyme; in most species, its subunits are encoded by a small multigene family (Cramer et al, 1989;Wanner et al, 1995). Arabidopsis has four PAL members (Wanner et al, 1995;Raes et al, 2003): Three (PAL1, PAL2, and PAL4) exhibit a high binding affinity for Phe and are associated with both the soluble phenolic and tissuespecific lignin synthesis (Rohde et al, 2004;Huang et al, 2010). By contrast, PAL3 has much lower in vitro catalytic efficacy than the other three isozymes and its biological function remains unclear (Cochrane et al, 2004).…”
Section: Introductionmentioning
confidence: 99%